ELEVATING FINANCIAL PERFORMANCE IN MUSLIM CLOTHING SMES BY LEVERAGING HUMAN RESOURCE CAPABILITIES AND CORPORATE STRATEGY - Dinda Fatmah; Mirhamida Rahmah; Yusriyah Rahmah; Syaiful Hasani; Chamdan Purnama (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2024)
Abstract: This research investigates the impact of external dynamics, human capital, business strategy, and innovation capability on the financial outcomes of Muslim clothing SMEs in East Java, Indonesia. Utilizing a quantitative approach with a descriptive research design, the study employs Structural Equation modelling (SEM) for data analysis. Data were gathered through surveys targeting managers of Muslim clothing SMEs in five regions of East Java, selecting 200 managers with at least two years of managerial experience using judgment sampling. The survey collected information on demographics, organisational experience, and perceptions regarding key variables. The results indicate that human capital positively affects financial outcomes but does not directly influence innovation capability. Business strategy significantly impacts both financial outcomes and innovation capability. Furthermore, a positive correlation is observed between financial outcomes and innovation capability. These findings highlight the necessity of enhancing human capital and implementing effective strategies to boost performance and innovation within SMEs. This study contributes to the academic literature by establishing financial outcomes as a mediator and external dynamics as a moderator in these interactions. However, the study’s emphasis on a specific region and industry may limit its generalizability. Future research should explore additional factors that affect innovation and performance and broaden the analysis to different sectors for a more extensive understanding. Abstrak: Penelitian ini meneliti dampak dari dinamika eksternal, sumber daya manusia, strategi bisnis, dan kemampuan inovasi terhadap hasil keuangan UKM pakaian Muslim di Jawa Timur, Indonesia. Menggunakan pendekatan kuantitatif dengan desain penelitian deskriptif, penelitian ini menggunakan Structural Equation Modelling (SEM) untuk analisis data. Data dikumpulkan melalui survei yang menargetkan manajer UKM pakaian Muslim di lima wilayah di Jawa Timur, dengan memilih 200 manajer dengan setidaknya dua tahun pengalaman manajerial menggunakan judgement sampling. Survei ini mengumpulkan informasi tentang demografi, pengalaman manajerial, dan persepsi mengenai variabel-variabel kunci. Hasil penelitian menunjukkan bahwa sumber daya manusia secara positif mempengaruhi hasil keuangan tetapi tidak secara langsung mempengaruhi kemampuan inovasi. Strategi bisnis secara signifikan mempengaruhi hasil keuangan dan kemampuan inovasi. Selain itu, korelasi positif diamati antara hasil keuangan dan kemampuan inovasi. Temuan ini menyoroti perlunya meningkatkan sumber daya manusia dan menerapkan strategi yang efektif untuk meningkatkan kinerja dan inovasi di UKM. Studi ini berkontribusi pada literatur akademis dengan menetapkan hasil keuangan sebagai mediator dan dinamika eksternal sebagai moderator dalam interaksi ini. Namun, penekanan studi ini pada wilayah dan industri tertentu dapat membatasi kemampuan generalisasinya. Penelitian di masa depan harus mengeksplorasi faktor-faktor tambahan yang memengaruhi inovasi dan kinerja dan memperluas analisis ke berbagai sektor untuk pemahaman yang lebih luas.